The constituents introduced by theming markers in French in the face of anteposed spatio-temporal complements : a prosodic analysis - Velghe, Tom (Journal of Speech Sciences, 2021)
This paper discusses the prosodic properties of sentence-initial spatio-temporal adverbials and of PPs introduced by so-called 'thematic markers' (TMCs), such as en ce qui concerne ('as for') or du point de vue de ('with regard to'). Their function is to indicate the aboutness-topic (a.o. Reinhart 1981, Gundel 1989, Lambrecht 1994) (1) or the topic Chinese style (Chafe 1976) (2). (1) Concernant le programme, il doit différer selon les universités et les profs. (2) Mais quand on peut il faut impérativement regarder BBC News. En ce moment, au niveau de l'info, ils sont vraiment au top. (YCCQA, De Smet 2009) Mertens (2008) hypothesizes that in certain syntactic constructions such as left dislocations, (pseudo-)clefts and certain adjuncts, the articulation between the left detached element (the dislocated element, the focus of the cleft, the adjunct) and the main clause is followed by a major prosodic boundary, i.e. they end on a relative high pitch level. It appears from our corpus that most TMCs end on such a major prosodic boundary (73%). As for sentence-initial spatio-temporal PPs, only 41% end on a major prosodic boundary. There are two important differences between TMCs and sentence-initial spatio-temporal PPs which explain that a strong prosodic boundary at the end of a TMC is more frequent than at the end of sentence-initial spatio-temporal adverbials. Semantically, sentence-initial spatio-temporal adverbials always limit the application range of the main clause, but not all TMCs affect the truth values of the proposition. Some can be omitted without changing the signification of the clause. On the syntactic level, sentence-initial spatio-temporal adverbials can always appear in the scope of a cleft or can be moved towards the end of the utterance without the proposition becomes ungrammatical. TMCs which affect the truth values of the proposition can also appear in the scope of the cleft or can be moved to the end of the proposition. TMCs which do not affect the truth values of the proposition do not allow these syntactic tests. Possibility of clefting, movement and specification of the main clause are used as tests (a.o. Melis 1983, Blanche-Benveniste et al. 1990) to show whether a constituent is linked to the verb phrase. This paper shows that sentence-initial spatial-temporal PPs are linked to the verb phrase, but that this is not the case for all TMCs. These syntactic and semantic observations explain the high frequency of the strong prosodic boundary at the end of a TMC.